Chapter 3 Daemonization The Strange Freedom: The Turn of the Screw and the Pamela Controversy - Jiménez Heffernan, Julián (Taylor & Francis, 2023)
Chapter 3 - ABSTRACT: An ironic response to Richardson's Pamela, The Turn of the Screw examines questions of moral hypocrisy and status inconsistency. Adopting a Fielding position, James celebrates the exemptions of a liberal conversation-or contemplation-premised both on the protection of adult secrets and the rejection of a Puritan education that prevents children from having free access to the open adult world. The first condition is represented by the detached master, an emblem of liberal privacy. The second is enforced by the governess' sadistic impulse to have the children see what they should never see-first, that the social hierarchies can be upset, and second, that a base menial enjoys the "strange freedom" to sexually approach a governess.